Design of compact multi‐band meander‐line antenna for global positioning system/wireless local area network/worldwide interoperability for microwave access band applications in laptops/tablets. Issue 15 (1st December 2016) - Bartwal, Pallavi; Gautam, Anil Kumar; Singh, Anil Kumar; Kanaujia, Binod Kumar; Rambabu, Karumudi
Abstract : In this study, a compact (15 mm × 12 mm) uniplanar multi‐band antenna is proposed for laptops and tablets application with a near omni‐directional coverage. The main structure of the antenna implements meander design for compactness and multi‐band operation. A staircase‐type arm and an F‐shaped arm are added for achieving resonances at exact frequencies and for good impedance matching, respectively. The antenna is designed such that it operates in all the global positioning system/wireless local area network/worldwide interoperability for microwave access bands and is easy to fabricate and integrate inside laptops/tablets. A prototype of the proposed antenna is fabricated, and its performance is validated for multi‐band operation and omni‐directional radiation.